La memoria espectral: problemas en torno a la restitución histórica de la cárcel de Carabanchel (Madrid, 1944-2008): The Spectral Memory: Challenges Surrounding the Historical Restoration of Carabanchel Prison (Madrid, 1944-2008) - Moriente Díaz, David (Artigrama, 2024)
Resumen El artículo reflexiona sobre los obstáculos para estudiar, proteger y conservar las cárceles construidas en España entre los siglos XIX y XX, con el fin de establecer una categoría de bien de interés cultural —todavía inexistente— de patrimonio carcelario. Dicha problemática se traza mediante el hilo conductor de la desaparecida Prisión Provincial de Hombres de Madrid, más conocida como cárcel de Carabanchel (1944-2008) a la que el autor del texto le ha asignado la formulación de “memoria espectral”; se trazará una panorámica somera sobre el estudio de la arquitectura carcelaria, su relación con la memoria y la historia, las dificultades para su patrimonialización y, finalmente, el estatus ontológico de la cárcel de Carabanchel en tanto que imagen residual de un edificio derribado tras su obsolescencia funcional. Abstract The article contemplates the impediments encountered in the study, preservation, and conservation of correctional facilities erected in Spain during the 19th and 20th centuries, with the objective of delineating a classification as a cultural asset within the realm of carceral heritage —a designation currently absent—. This inquiry is conducted through an exploration centered on the defunct Prisión Provincial de Hombres de Madrid, colloquially known as Carabanchel prison (1944-2008), which has been imbued by the author of the text with the concept of “spectral memory”; a concise examination is conducted regarding the analysis of prison architecture, its nexus with collective memory and historical narratives, the challenges associated with its heritage designation, and finally, the existential essence of Carabanchel prison as a lingering image of a structure dismantled following its functional obsolescence. Keywords Carabanchel Prison, carceral architecture, heritage preservation process, carceral heritage, historical memory, spectral memory.